Pelatihan Peningkatan Kualitas Sumber Daya Manusia Dengan Microsoft Word Di Kalangan SMA - Irawati, Riri; Pradana, Rizky; Puspasari, Indah (Ikatan Ahli Informatika Indonesia, 2024)
Information and Communication Technology (ICT) nowadays is very much needed by high school (SMA) students, so this information really requires training in the use of technology and communication devices so that later students can make good use of it. Many students cannot use Microsoft Word because it is not taught at school, there is a lack of computer equipment or the high cost of computer courses. It is hoped that with this training, students will be able to know more about techniques for using Microsoft Word. This training activity includes a pre-test, providing material, evaluation and post-test. Based on the Pre-test and Post-test scores, there was an increase in participants' scores on Microsoft Word training. This can be seen from the average score of participants before training for Microsoft Word training which was 43.5 and the average post test score was 74.2. Looking at the average results, it can be concluded that the participants experienced an increase in scores of 30.7 or 58.6%. Keywords: Microsoft Word, Information and Communication Technology, Pre test, Post test, Computer